Health professional perspectives on translation of cultural safety concepts into practice: A scoping study - Wilson, Lynere; Wilkinson, Amanda; Tikao, Kelly (Frontiers in Rehabilitation Sciences, 2022)
People from unique and diverse populations that is social groupings excluded by the dominant majority by, for example, ethnicity, gender, age, sexual orientation, disability or even rurality), experience dissimilar health outcomes. Members of such populations who live with long-term health conditions suffer further health disparities through inefficient management and treatment. This remains a significant limitation to achieving equity in health outcomes. Being responsive and acting upon the cultural needs of unique and diverse populations within health services is pivotal in addressing health disparities. Despite provision of professional training to health professionals, cultural competency remains an elusive goal. This scoping study summarized available literature about what helped health professionals translate cultural safety concepts into practice. Electronic databases were surveyed using MeSH terms and keywords for English language articles and reference lists of potentially included studies. Quality appraisal was undertaken using Joanna Briggs Institute critical appraisal tools. Data were charted, with a descriptive numerical summary and thematic analysis of study findings undertaken. Twelve qualitative studies with n=206 participants were included. Learning through and from direct experience, and the individual qualities of professionals (i.e., individual capacity for relational skills and intentionality of engagement with one’s own values and biases) facilitated translation of cultural safety concepts into practice. Also important was the need for cultural training interventions to address both issues of content and process within course design. Doing this would take into consideration the benefits that can come from learning within a group context. In each of these themes was evidence of how health professionals needed the ability to manage emotional discomfort as part of the process of learning. A dearth of information exists exploring professionals’ perspectives on translating cultural safety concepts into practice. There may be merit in designing educational interventions that look beyond the classroom. We also suggest that nurturing people’s relational skills likely holds benefits to growing culturally safe practice as does increasing health professional’s capacity to sit with the discomfort that occurs when paying attention to one’s own and others values and biases.